Rgp1 contributes to craniofacial cartilage development and Rab8a-mediated collagen II secretion - Ritter, Dylan J.; Choudhary, Dharmendra; Unlu, Gokhan; Knapik, Ela W. (Frontiers in Endocrinology, 2023)
Rgp1 was previously identified as a component of a guanine nucleotide exchange factor (GEF) complex to activate Rab6a-mediated trafficking events in and around the Golgi. While the role of Rgp1 in protein trafficking has been examined in vitro and in yeast, the role of Rgp1 during vertebrate embryogenesis and protein trafficking in vivo is unknown. Using genetic, CRISPR-induced zebrafish mutants for Rgp1 loss-of-function, we found that Rgp1 is required for craniofacial cartilage development. Within live rgp1-/- craniofacial chondrocytes, we observed altered movements of Rab6a+ vesicular compartments, consistent with a conserved mechanism described in vitro. Using transmission electron microscopy (TEM) and immunofluorescence analyses, we show that Rgp1 plays a role in the secretion of collagen II, the most abundant protein in cartilage. Our overexpression experiments revealed that Rab8a is a part of the post-Golgi collagen II trafficking pathway. Following loss of Rgp1, chondrocytes activate an Arf4b-mediated stress response and subsequently respond with nuclear DNA fragmentation and cell death. We propose that an Rgp1-regulated Rab6a-Rab8a pathway directs secretion of ECM cargoes such as collagen II, a pathway that may also be utilized in other tissues where coordinated trafficking and secretion of collagens and other large cargoes is required for normal development and tissue function.